The Covenant of Peace: A Neglected Ancient Near Eastern Motif - Batto, Bernard F.
mentions Gen 8:21-22, Atr. III v 2-4, Gilg. XI 163-169 as containing divine oaths. Signs accompanying oaths: Atr. III v 46 - vi 4, Gilg. IX 163-165, CTA 3 of Baal cycle.